Appropriate technology of Traditional Chinese and western medicine based on the concept of enhanced recovery after surgery in total knee arthroplasty (基于加速康复外科理念的中西医结合护理在全膝关节置换术中的应用) - WANG Qiujie (王秋洁); TIAN Runxi (田润溪); FAN Weiwei (范薇薇); TANG Ling (唐玲); DAI Shuang (戴爽); ZHANG Qian (张倩); HE Xin (何欣); ZHANG Jianmeng (张建萌) (Journal of International Translational Medicine Limited, 2023)
The enhanced recovery after surgery (ERAS)has been widely applied in the treatment of rehabilitation of patient with total knee arthroplasty (TKA). The ERAS has been proved to be effective in relieving pain, shortening the length of hospital stay, reducing economic and social healthcare costs. By reviewing literatures, this paper summarized the application of appropriate technology of Traditional Chinese and western medicine based on the concept of ERAS in TKA, and provided reference for improvement of perioperative nursing of TKA. (近年来, 加速康复外科(ERAS)理念在骨科全膝关节置换术(TKA)患者治疗和康复中得到了应用和普及, 基于ERAS的干预能够减轻患者痛苦, 缩短住院周期, 节约经济成本和社会医疗资源成本。本文通过文献搜索, 归纳总结基于ERAS理念的中西医结合护理干预在TKA围手术期中的应用, 旨在为提升TKA护理质量提供参考。)